Exploring Empathy In A Dentist-Patient Relationship. Conclusions From Qualitative Exploratory Research Of Practicing Dentists - Orakzai, Gulmina Saeed; Jamil, Brekhna (Journal of Rawalpindi Medical College, 2023)
Objective: This study explored the factors influencing the development of empathy in a dentist-patient relationship. Design: An exploratory qualitative study. Place and duration of the study: Khyber Medical University KPK, Pakistan October 2019 to April 2020.was conducted during 2019-2020 Methodology: This exploratory qualitative study was conducted during 2019-2020. It was conducted on 12 dental surgeons, recruited from four major dental clinical specialties. A purposive sampling technique was used. In-depth interviews were conducted through a semi-structured format. The interviews were audio recorded, transcribed verbatim and analyzed, using the thematic analysis framework. Results: Three themes were extracted from data. 1) Institutionalization of empathy, indicating a need for incorporating empathy in undergraduate and postgraduate dental curriculum, 2) Barriers in the path of empathetic attitude, including a variety of factors hampering the development of empathy in a dentist-patient relationship and 3) Cultivating a Culture of empathy for better health care provision, indicating a need for changing the collective attitude of all health care professionals, administrative staff, and students. The participants of the study observed that development of empathy in a dentist-patient relationship includes a wide range of factors, ranging from curricular, personal, social, organizational, and cultural. These factors elaborate that empathy is a multidimensional phenomenon with roots deeply entrenched in professional and personal domains.